HUBUNGAN KECERDASAN VISUAL-SPASIAL DENGAN KEMAMPUAN MENGGAMBARKAN BENTUK MOLEKUL PADA MAHASISWA - Apecawati, Linda Dwi; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this correlation study were 1) to measure students spasial-visual intelligence, 2) to measure students skill on drawing geometry of molecules and 3) to determine whether there was a significant relation between them. The subjects in this study were 65 students of Chemistry Education Program 2014/2015 FKIP UNTAN. The data in this study were collected from achievements test and spasial visual intelligence test. The results showed that the ability of students on drawing geometry of molecules were excellent (45,70 % ). On the other hand spatial visual intelligence of students were good (63,24%). According to Spearman-Brown nonparametric statistics test, there was significant a relationship between spatial visual intelligence of students and skill on drawing geometry of molecules, although their relationship was poor (0,309). Keywords: Visual-Spatial Intelligence, Skill on Drawing, Geometry of Molecules, Correlation